Kosmologi Budaya Jawa dalam Tafsîr al-Ibrîz Karya KH. Bisri Musthofa - Maslukhin, M (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
This article discusses the literature interpretation production Bisri Musthofa (1915-1977 AD), entitled al-Ibrîz li Ma‘rifat Tafsîr al-Qur’ân al-‘Azîz. As a work of interpretation, al-Ibrîz packaged in the form of prose and using low Javanese language as the language of his introduction. At the theoretical level, low Javanese language choice is an option that does not mess around, because through that way Bisri Musthofa should risking authority in expressing the totality of his work. However, the problem of whether the arrangement and selection of diction to bang and play with the reader’s emotions, al-Ibrîz have really paid attention to the culture and cosmology Java adequately? Whether that interpretation can also be “in addition to” scientific work as well as the interpretation of literary works that contain Java defense of the existence of all Javanese? In addition, al-Ibrîz that in fact the result of a thought Bisri when interacting with the text of the Koran can not be separated from the goals, interests, experiences and socio-political circumstances surrounding them, so it is legitimate to question whether al-Ibrîz relevant to the demands of his time or not? In this context, this article was written.